Assessment Framework for People-Centred Solutions to Carbon Neutrality A Comprehensive List of Case Studies and Social Innovation Indicators at Urban Level - Bresciani, Sabrina; Rizzo, Francesca; Mureddu, Francesco (PoliMI SpringerBriefs,, 2024)
This open access book presents a catalogue of over one thousand indicators which can be used by cities' public administrators to monitor and evaluate social innovation action plans to support people-centred, collaborative or co-designed solutions to lower carbon emissions. Indicators are clustered according to a framework of social innovation solutions for climate neutrality at city level, developed by merging top-down academic knowledge with bottom-up pragmatic case studies. There is currently limited guidance on how to embed social innovations in their cities' action plans with the aim of reaching climate neutrality, and on how to assess the progress and impacts of such people-centred projects in cities. The book addresses this gap and is thus relevant for scholars in the field of policy-making and design, as well as cities' transition teams, policymakers and consultants. Based on the work developed within the EU-funded project NetZeroCities, intervention logics are provided for each of the ten categories of action, with related indicators clustered by category and evaluation criteria (effectiveness, efficiency, relevance, replicability, and scalability). Guidelines to implement the framework support city administrators in defining steps they need to follow to apply the indicators to their local case, making social innovation a crucial lever for accelerating systemic transformation. .